Dysfunctional regulation of pivotal and key inflammatory pathways in infertile Indian women with genital tuberculosis. (4th October 2022) - Parikh, Firuza R.; Panpalia, Madhavi; Mehta, Trupti; Agarwal, Sapna; Khandeparker, Meenal; Chettiar, Shiva Shankaran; Patel, Alpesh; Jhala, Devendrasinh D.; Chettiar, Venkatlaxmi; Parikh, Swapneil
Abstract: Problem: Diagnosis of female genital tuberculosis (FGTB) remains elusive due to the paucibacillary nature of the disease. We evaluated if analysis of inflammatory pathways of endometrial tissue could establish a better diagnosis of FGTB. Method of Study: One hundred and four infertile women suspected of having GTB or having been treated for GTB in the past, underwent endometrial biopsies for diagnosis and Gene Inflammatory Pathways analysis at our center between 2018–2020. Diagnosis of FGTB was based on acid‐fast bacilli culture, immunocytochemistry, nested‐polymerase chain reaction, histopathological examination, TB GeneXpert, or combinations thereof. Gene expression profiles were also analyzed. Results: Based on diagnostic tests of 104 women, 44 (42%) were considered TB‐positive, 35 (34%) TB‐negative, and 25 (24%) TB‐negative after TB treatment in the past. Inflammatory pathways were significantly upregulated in TB‐positive women versus TB‐negative (41% vs. 6%; p = .0005), and in women who were TB‐negative after TB treatment in the past versus TB‐negative (never treated for TB in the past) (38% vs. 6%; p = .0037). Two‐hundred seventy‐one genes were upregulated, and 61 genes were downregulated in TB‐positive women versus those who were TB‐negative. Differentially expressed genes were mapped to various interlinked inflammatory signaling pathways, including mitogen‐activated protein kinase (MAPK), Natural Killer (NK) cells, nuclear factor kappa‐B (NF‐kB), tumor necrosis factor (TNF), and Toll‐like receptors (TLR) signaling. Conclusions: Inflammatory pathways and gene expression profiles add to the diagnostic tools to identify TB‐positive women at an early stage. The results from this study are still experimental and large multi‐centric studies are suggested before their recommendation in routine clinical practice.